Integrated CMS Website Implementation With The Codeigniter Framework - Febrizal Alfarasy Syam; Yuvi Darmayunata; Afriansyah Afriansyah (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
Content Management System (CMS) is a system or software in developing content. What is meant by content is all forms of digital information, in the form of image files, audio, video, text and other computer files. CMS makes it easy to create attractive website pages without having to understand how to create a website from scratch. Likewise, Lancang Kuning University has created an Integrated CMS website or integrated with faculty websites at Lancang Kuning University, by creating one database but the frontend and backend templates can be customized as desired. With this integrated website, it will make it easier for the main admin and faculty admin to maintain the website, including in its development. This website was built using the concept of Object Oriented and using a codeigniter framework.C